The Rhetoric of War – Ex Yugoslavia example - Kišiček, Gabrijela (2013)
Disintegration of Yugoslavia resulted with war involving Croatia, Serbia and Bosnia. Although war ended in 1995 there are still unsolved issues concerning the cause, responsibility and quilt for more than 2 million refuges (both in Croatia and Bosnia) and more than 200 000 dead. This paper aims to determine characteristics of rhetoric in political discourse preceding the war. Speeches analyzed were delivered in the period of 1989 until 1992. We analyzed 20 speeches of dominant political figures from Croatia, Serbia and Bosnia (Franjo Tuđman, Gojko Šušak, Slobodan Milošević, Radovan Karadžić, Vojislav Šešelj and Alija Izetbegović) aiming to find argumentation strategies in their speeches (especially usage of topoi considering national questions), system of value, and other rhetorical characteristics and dimensions of persuasion which could show certain similarities and differences between the leaders of three nations. Analysis of argumentation was based on several argumentation handbooks (Weston 1992, Rieke and Sillars 2001, Walton 2004, Tindale 2007). We believed that political leaders will have different argumentation strategies and different system of value since they represented different nations (with different historical background and cultural heritage) and different religions. Results of analysis show however that there are many similarities in argumentation strategies and frequent usage of fallacies (argumetum ad populum, red herring, argumentum ad baculum, hasty generalizations etc.) between analyzed speakers. The main goal of this paper and contribution to the rhetoric of citizenship is determining means of persuasion using analytical tools from rhetoric in order to describe what might be called The Rhetoric of War.
ENG